Microbial communities in seawater from an Arctic and a temperate Norwegian fjord and their potentials for biodegradation of chemically dispersed oil at low seawater temperatures. Issue 1 (April 2018) - Ribicic, Deni; Netzer, Roman; Winkler, Anika; Brakstad, Odd Gunnar
Abstract: Biodegradation of chemically dispersed oil at low temperature (0–2 °C) was compared in natural seawater from Arctic (Svalbard) and a temperate (Norway) fjords. The oil was premixed with a dispersant (Corexit 9500) and small-droplet oil dispersions prepared. Faster biotransformation of n -alkanes in the Arctic than in the temperate seawater were associated with the initially higher abundance of the alkane-degrading genus Oleispira in the Arctic than the temperate seawater. Comparable transformation of aromatic hydrocarbons was further associated with the late emergences Cycloclasticus in both seawater sources. The results showed that chemically dispersed oil may be rapidly biodegraded by microbial communities in Arctic seawater. Compared to oil biodegradation studies at higher seawater temperatures, longer lag-periods were experienced here, and may be attributed to both microbial and oil properties at these low seawater temperatures. Highlights: Chemically dispersed oil was rapidly biotransformed in cold Arctic seawater. The bacterial genera Oleispira and Cycloclasticus were involved in degradation. n -Alkanes were faster transformed in the Arctic than in a temperate seawater. Aromatic PAH was transformed at comparable rates in both seawaters. Different communities in the seawater affected hydrocarbon degradation.